2022
DOI: 10.1515/bot-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod and temperature on ecophysiological responses of Ericaria barbatula (Phaeophyceae): a long-term study

Abstract: The photoperiod alone or in combination with temperature may affect macroalgal growth, reproduction, and development. This study aimed to investigate the responses of Ericaria barbatula, a perennial fucalean species collected from Kavala Gulf, Greece, to photoperiod and temperature. Maximum quantum yield (F v /F m ), wet biomass (g), relative growth rate (day−1), and reproduction (receptacles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Orfanidis (1991) showed that Gongolaria barbata (as former Cystoseira barbata) from the northern Aegean Sea was able to survive between -1°C and 30°C, growing optimally between 10°C and 20°C; he was, however, not able to induce fertility in the specimens used for his experiments. Recently, Papadimitriou et al (2022), based on laboratory experiments, demonstrated that in Ericaria barbatula (Kützing) Molinari & Guiry formation of receptacles and fertilization took place only in short day conditions. This was the first study documenting a photoperiodic effect in a Mediterranean Cystoseira s.l.…”
Section: Discussionmentioning
confidence: 99%
“…Orfanidis (1991) showed that Gongolaria barbata (as former Cystoseira barbata) from the northern Aegean Sea was able to survive between -1°C and 30°C, growing optimally between 10°C and 20°C; he was, however, not able to induce fertility in the specimens used for his experiments. Recently, Papadimitriou et al (2022), based on laboratory experiments, demonstrated that in Ericaria barbatula (Kützing) Molinari & Guiry formation of receptacles and fertilization took place only in short day conditions. This was the first study documenting a photoperiodic effect in a Mediterranean Cystoseira s.l.…”
Section: Discussionmentioning
confidence: 99%